2009
DOI: 10.1590/s0036-46652009000600005
|View full text |Cite
|
Sign up to set email alerts
|

Serological evidence of Rickettsia parkeri as the etiological agent of rickettsiosis in Uruguay

Abstract: SUMMARYWe report three new rickettsiosis human cases in Uruguay. The three clinical cases presented clinical manifestations similar to previous reported cases of Rickettsia parkeri in the United States; that is mild fever (< 40 o C), malaise, headache, rash, inoculation eschar at the tick bite site, regional lymphadenopathy, and no lethality. Serological antibody-absorption tests with purified antigens of R. parkeri and Rickettsia rickettsii, associated with immunofluorescence assay indicated that the patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 16 publications
(19 reference statements)
2
20
0
3
Order By: Relevance
“…Amblyomma triste has been found infected by Rickettsia parkeri in Argentina, Brazil and Uruguay (Venzal et al 2004;Silveira et al 2007;Nava et al 2008), where cases of human disease attributed to this rickettsia have been diagnosed (Conti-Díaz et al 2009;Moraes-Filho et al 2009;Romer et al 2011). In our study, adults of A. triste were found on B. dichotomus, H. hydrochaeris and S. scrofa.…”
Section: Discussionsupporting
confidence: 46%
“…Amblyomma triste has been found infected by Rickettsia parkeri in Argentina, Brazil and Uruguay (Venzal et al 2004;Silveira et al 2007;Nava et al 2008), where cases of human disease attributed to this rickettsia have been diagnosed (Conti-Díaz et al 2009;Moraes-Filho et al 2009;Romer et al 2011). In our study, adults of A. triste were found on B. dichotomus, H. hydrochaeris and S. scrofa.…”
Section: Discussionsupporting
confidence: 46%
“…Finally, in 2011, Romer et al reported the first human cases of spotted fever caused by R. parkeri in Argentina, which were characterized by fever, rash, inoculation eschar, lymphadenopathy, and no deaths, similar to the clinical illness caused by R. parkeri in the United States (68,171). Similar clinical manifestations, also associated with A. triste, have been reported since the 1990s in Uruguay, where at least two of these cases were attributed to R. parkeri through cross-absorption (CA) serologic tests (172).…”
Section: South Americamentioning
confidence: 69%
“…For example, R. rickettsii infection can be acquired in Canada and Mexico, as well as in Central America and South America, where cases are reported from Costa Rica, Panama, Brazil, Colombia, and Argentina (253)(254)(255)(256)(257)(258)(259)(260). R. parkeri infections have been described in Uruguay, Brazil, and Argentina (38,253,261,262). Human anaplasmosis has been reported from several countries throughout Europe (263), as well as from several Asian countries, including China, Korea, Russia, and Japan (264)(265)(266)(267).…”
Section: Travel Outside Of the United Statesmentioning
confidence: 99%